2023
DOI: 10.1186/s12957-023-03005-w
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative anemia and long-term survival in patients undergoing colorectal cancer surgery: a retrospective cohort study

Abstract: Background The impact of preoperative anemia on a survival outcome and the importance of correcting preoperative anemia in patients with colorectal cancer (CRC) remain controversial. This study aimed to explore how preoperative anemia affects the long-term survival of patients undergoing colorectal cancer surgery. Methods This was a retrospective cohort study in which adult patients underwent surgical resection for colorectal cancer between January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Numerous studies have suggested that the higher the pathological stage of CRC, the higher the probability of anemia ( Lipton et al, 2021 ; Väyrynen et al, 2018 ). A recent study has highlighted that anemia incidence in CRC patients with Dukes stage C and D is up to 60%–75% ( Deng, Weng & Zhang, 2023 ). According to statistics, the incidence of anemia in patients with gastrointestinal tumors in China is 51.13%, and more than 90% of them have not been given any treatment to correct anemia before finding a malignant tumor ( Ciardiello et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have suggested that the higher the pathological stage of CRC, the higher the probability of anemia ( Lipton et al, 2021 ; Väyrynen et al, 2018 ). A recent study has highlighted that anemia incidence in CRC patients with Dukes stage C and D is up to 60%–75% ( Deng, Weng & Zhang, 2023 ). According to statistics, the incidence of anemia in patients with gastrointestinal tumors in China is 51.13%, and more than 90% of them have not been given any treatment to correct anemia before finding a malignant tumor ( Ciardiello et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…
y influenced by various factors, including genetics, environment, and lifestyle [7][8][9]. Although treatment methods have improved in recent years, long-term survival rates for CRC patients remain unsatisfactory [10][11][12]. Standard treatment options, including surgery, radiotherapy, chemotherapy, and targeted therapy, often come with risks of side effects and recurrence [13,14].
…”
mentioning
confidence: 99%